“AMIR TEMUR AS A STATE BUILDER AND MILITARY LEADER” - Teshaboyeva Nafisa Zubaydulla qizi,; Qaxramonova Nuridiyda Jaxongir qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract Amir  Temur,  often  remembered  as  Tamerlane, remains  a  figure  of  profound historical complexity, simultaneously lauded as a brilliant military strategist and state builder,  and  condemned  as  a  ruthless  conqueror.  This  article  critically  examines Temur's  multifaceted  legacy,  analyzing  his  contributions  to  statecraft,  military innovation, and cultural patronage against the backdrop of the extensive human cost of his campaigns. It investigates the scholarly debates surrounding the authenticity and interpretive value of primary sources, particularly the contested Tuzukat-i Timuri, and explores  how  these  discussions  shape  contemporary  understandings  of  Temur's governance principles. By synthesizing existing academic perspectives and addressing the inherent dualities of his rule, this analysis seeks to reconcile the images of Temur as  both  a  constructive  force  for  state  consolidation  and  a  destructive  agent  of widespread  devastation.  The  article  aims  to  offer  a  nuanced  understanding  of  his enduring influence, particularly in modern national narratives.